Topical Bixin Confers NRF2-Dependent Protection Against Photodamage and Hair Graying in Mouse Skin - Rojo de la Vega, Montserrat; Zhang, Donna D.; Wondrak, Georg T. (Frontiers in Pharmacology, 2018)
Environmental exposure to solar ultraviolet (UV) radiation causes acute photodamage, premature aging, and skin cancer, attributable to UV-induced genotoxic, oxidative, and inflammatory stress. The transcription factor NRF2 is the master regulator of the cellular antioxidant response protecting skin against various environmental stressors including UV radiation and electrophilic pollutants. NRF2 in epidermal keratinocytes can be activated using natural chemopreventive compounds such as the apocarotenoid bixin, an FDA-approved food additive and cosmetic ingredient from the seeds of the achiote tree (Bixa orellana). Here, we tested the feasibility of topical use of bixin for NRF2-dependent skin photoprotection in two genetically modified mouse models [SKH1 and C57BL/6J (Nrf2+/+ versus Nrf2-/-)]. First, we observed that a bixin formulation optimized for topical NRF2 activation suppresses acute UV-induced photodamage in Nrf2+/+ but not Nrf2-/- SKH1 mice, a photoprotective effect indicated by reduced epidermal hyperproliferation and oxidative DNA damage. Secondly, it was demonstrated that topical bixin suppresses PUVA (psoralen+UVA)-induced hair graying in Nrf2+/+ but not Nrf2-/- C57BL/6J mice. Collectively, this research provides first in vivo evidence that topical application of bixin can protect against UV-induced photodamage and PUVA-induced loss of hair pigmentation through NRF2 activation. Topical NRF2 activation using bixin may represent a novel strategy for human skin photoprotection potentially complementing conventional sunscreen-based approaches.